Florística e estrutura em ambiente de borda-interior em remanescente de Floresta Ombrófila Densa das Terras Baixas - Dias, Patrícia Borges (2019)
The Atlantic Forest is one of the most biodiversity-rich environments in the world. Among its phytophysiognomies is the Lowlands Rain Forest, strongly fragmented by the various forms of land use occupation, even inside protected areas. In addition to the reduction of its original area, fragmentation brings with it the edge effect, which influences the ecological processes of the remnants. The objective of this study was to evaluate the floristic composition and the horizontal structure of the woody plant community in the interior and in the edges in contact with different boundaries in a remnant of Lowlands Rain Forest in the Córrego Grande Biological Reserve, Conceição da Barra, ES. For this, we tested the hypothesis that these variations occur along an environmental and biological gradient of change. For vegetation sampling, 36 plots (10 m x 25 m) totaling 0.9 ha were allocated, distributed over two edges with different boundaries (dirt road and forest edge) and inside the remainder. All individuals with breast height diameter = 2.5 cm were measured and identified. The phytosociological parameters, Shannon diversity index and Pielou equability, as well as the Bray-Curtis similarity index and the UPGMA grouping were calculated to verify the similarity between the interior and the edges studied. For the determination of the species that characterize the floristic groupings of the study area, the Analysis of Indicating Species (ISA) was carried out. The percentage of canopy opening was obtained through two hemispherical digital photographs, collected per plot in the months of April and September and analyzed by Gap Ligth Analyzer Mobile app - GLAMA software. The chemical characterization of the soil surface layer (0 - 20 cm) was carried out. The subsamples were collected in five points, distributed at the vertices and inside each plot, and later homogenized resulting in a sample composed of sample unit. For the analysis of density and humidity, three undisturbed samples were collected per plot. Using the penetrometer equipment, the penetration resistance of the soil was calculated by the number of beats collected at five points of each plot until reaching 20 cm depth. To verify the influence of the environmental factors on the vegetation, Redundancy Analysis (RDA) was performed. The remnant presented a great wealth of species in the area, with taxa in categories of extinction risk, besides possible new records for the state. The ReBio interior is more similar to the forest edge. It was observed that the distribution pattern of the species was influenced by the environmental variables (canopy opening, moisture and sodium) and spatial variables, and the first three axes of the RDA explained 42.08% of the variation in the floristic composition of the woody community. The results confirm that some species have environmental preferences in the remnant.